Relation of Vegetarian Dietary Patterns With Major Cardiovascular Outcomes: A Systematic Review and Meta-Analysis of Prospective Cohort Studies - Glenn, Andrea J.; Viguiliouk, Effie; Seider, Maxine; Boucher, Beatrice A.; Khan, Tauseef A.; Blanco Mejia, Sonia; Jenkins, David J. A.; Kahleová, Hana; Rahelić, Dario; Salas-Salvadó, Jordi; Kendall, Cyril W. C.; Sievenpiper, John L. (Frontiers in Nutrition, 2019)
Background: Vegetarian dietary patterns are recommended for cardiovascular disease (CVD) prevention and management due to their favourable effects on cardiometabolic risk factors, however, the role of vegetarian dietary patterns in CVD incidence and mortality remains unclear. Objective: To update the European Association for the Study of Diabetes (EASD) clinical practice guidelines for nutrition therapy, we undertook a systematic review and meta-analysis of the association of vegetarian dietary patterns with major cardiovascular outcomes in prospective cohort studies that included individuals with and without diabetes using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Methods: MEDLINE, EMBASE, and Cochrane databases were searched through September 6th, 2018. We included prospective cohort studies ≥1 year of follow-up including individuals with or without diabetes reporting the relation of vegetarian and non-vegetarian dietary patterns with at least one cardiovascular outcome. Two independent reviewers extracted data and assessed study quality (Newcastle-Ottawa Scale). The prespecified outcomes included CVD incidence and mortality (total CVD, coronary heart disease (CHD) and stroke). Risk ratios for associations were pooled using inverse variance random effects model and expressed as risk ratios (RRs) with 95% confidence intervals (CIs). Heterogeneity was assessed (Cochran Q-statistic) and quantified (I2-statistic). The overall certainty of the evidence was assessed using GRADE. Results: Seven prospective cohort studies (197,737 participants, 8,430 events) were included. A vegetarian dietary pattern was associated with reduced CHD mortality (RR, 0.78 [CI, 0.69, 0.88]) and incidence (0.72 [0.61, 0.85]) but were not associated with CVD mortality (0.92 [0.84, 1.02]) and stroke mortality (0.92 [0.77, 1.10]). The overall certainty of the evidence was graded as “very low” for all outcomes, owing to downgrades for indirectness and imprecision. Conclusions: Very low-quality evidence indicates that vegetarian dietary patterns are associated with reductions in CHD mortality and incidence but not with CVD and stroke mortality in individuals with and without diabetes. More research, particularly in different populations, is needed to improve the certainty in our estimates. Registration: Clinicaltrials.gov, NCT03610828